The Impact of Training with Varying Intensities on the Specific Strength and Speed of the Anchor Runner in the 100-Meter Relay for Female Students - Muhsin, Zainab Qahtan Abdul (Indonesian Journal of Physical Education and Sport Science, 2025)
Study Purpose. The selection of this type of training was based on the performance results in the 100m relay for female athletes. As the researcher specializes in track and field training at the College of Physical Education and Sport Sciences for Women and has observed the athletes' performance in this event, she was motivated to investigate the impact of variable-intensity training on enhancing specific strength and speed. Therefore, a training program incorporating different intensity levels was designed to assess its effectiveness in developing these attributes. Material and methods. The study was carried out fourth-year female participants by selecting two groups: an experimental group and a control group. Pre-tests were conducted to both sets of participants before implementing the proposed training program for the experimental group, while the control group followed the conventional method. After applying the designed program, post-tests were conducted to evaluate the impact of training at varying intensities on the study variables. Results. The investigator determined that the training method utilizing varying intensities led to a significant improvement in specific strength, speed, and performance in the experimental group, underscoring the efficiency of this approach in enhancing athletic performance. Furthermore, the results confirmed the presence of notable statistical variations in favour of the experimental group, demonstrating superior performance in the 100-meter relay race. Conclusions. The researcher recommended applying this training approach to other track and field events to optimize the benefits of varying training intensities in enhancing athletic performance. The study contributes to the development of specific strength by employing training programs with varying intensity levels.